Multiple Mechanical Recycling of a Post-Industrial Flexible Polypropylene and Its Nanocomposite with Clay: Impact on Properties for Food Packaging Applications - Guarda-Moraga, A; Galotto-Lopez, M; Rojas-Sepulveda, A; Garrido-Ayala, L; Velasquez, E (Elsevier Ltd, 2024)
The development of polymer nanocomposites for food packaging has been increasing, but there is a lack of studies on their recyclability. The modification of the physical-mechanical properties and overall migration of post-industrial flexible recycled polypropylene (PIPP) and PIPP/compatibilizer/NI.44P clay nanocomposite with the simulated repetitive mechanical recycling were comparatively studied. The structure, thermal properties, crystallinity, and water vapor permeability of the nanocomposite were not significantly affected by multiple recycling (three re-extrsuion cyles). Among the mean findings, the melt flow rate of the polymer was the parameter more affected by the reprocessing, especially in the nanocomposite. PIPP and PIPP nanocomposite tended to molar mass reduction by repetitive reprocessing. However, a narrower molar mass distribution was obtained according to the rheological analysis. Clay addition significantly reduced the ductility of the films in the first reprocessing cycle but interestingly, the tensile properties for PIPP and nanocomposite were similar in the fourth cycle. Prominently, overall migration of the nanocomposite to olive oil diminished by reprocessing cycles, while the opposite was found for the PIPP without clay. Nonetheless, in all cases, the overall migration values to ethanol 10% and olive oil were below the maximum limit permitted for food packaging. © 2024 Elsevier Ltd